27 Are we overdiagnosing attention deficit hyperactivity disorder (ADHD)?. (4th December 2019) - Kazda, Luise; Thomas, Rae; Bell, Katy; McGeechan, Kevin; Barratt, Alexandra
Abstract : Objectives: The objective of this study is to use a recently developed framework of questions to systematically determine if the existing literature indicates a potential for overdiagnosis and overtreatment in ADHD. We hypothesize that ADHD fulfils the pre-determined criteria for overdiagnosis. A secondary aim of the study will be to examine and highlight any gaps in the current evidence that potentially prevent us from determining whether or not ADHD is overdiagnosed and overtreated. A further, secondary aim of the study will be to rigorously test the existing framework for its applicability and usability in another area. Method: We will use an existing framework of 5 questions, developed to identify early markers of potential overdiagnosis, to conduct a comprehensive scoping review of the existing literature on various aspects of previously published ADHD research. Results: This study is ongoing but will be completed in time to present the results at the Preventing Overdiagnosis Conference in December 2019. Results of the scoping review will be mapped to the framework published by Bell et al in 2019 (Bell KJL, Doust J, Glasziou P, Cullen L, Harris IA, Smith L, et al. Recognizing the Potential for Overdiagnosis: Are High-Sensitivity Cardiac Troponin Assays an Example? Ann Intern Med. 2019;170(4)) and attempt to provide the best possible answer to the five questions designed to assess the potential for diagnosis. These questions are: 1. Is there potential for increased diagnosis? 2. Is diagnosis actually increased? 3. Are additional cases subclinical or low risk? 4. Are additional cases treated? 5. Might harms outweigh benefits? Conclusions: We aim to present answers to both our primary and secondary study questions at the 58.